2015
DOI: 10.3389/fnhum.2015.00012
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gray matter volume after microsurgical lumbar discectomy: a longitudinal analysis

Abstract: People around the world suffer chronic lower back pain. Because spine imaging often does not explain the degree of perceived pain reported by patients, the role of the processing of nociceptor signals in the brain as the basis of pain perception is gaining increased attention. Modern neuroimaging techniques (including functional and morphometric methods) have produced results that suggest which brain areas may play a crucial role in the perception of acute and chronic pain. In this study, we examined 12 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…A possible explanation for the differences in results between our study and the study by Dowiasch et al ( 2015 ) comes from the fact that participants in their study were actively locomoting through the environment, while our participants were passively transported along the route. It is conceivable that age-related differences in postural control (Jimenez et al, 2016 ), control of locomotion and steering cause differences in gaze behaviour.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…A possible explanation for the differences in results between our study and the study by Dowiasch et al ( 2015 ) comes from the fact that participants in their study were actively locomoting through the environment, while our participants were passively transported along the route. It is conceivable that age-related differences in postural control (Jimenez et al, 2016 ), control of locomotion and steering cause differences in gaze behaviour.…”
Section: Discussioncontrasting
confidence: 89%
“…First, we focused on general gaze patterns during the learning phase. For the vast majority of measures, there were no differences between age groups, which was surprising, given evidence from Dowiasch et al ( 2015 ), who reported age differences in general gaze parameters. The bootstrapped t test analysis demonstrated that our observed comparisons fall well within the distribution of t values when comparing groups without differences, suggesting our results represent no difference between age groups as opposed to a type 2 error.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…For instance, after 3 to 4 weeks of pain rehabilitative treatment in pediatric complex regional pain syndrome, cortical thickness increased in regions implicated in pain modulation along with lower pain intensity. 26 In chronic low back pain, gray matter changed after microsurgical lumbar discectomy 46 in the basal ganglia and hippocampus; regions involved in motor, emotional, cognitive, and learning. 3,55 Reversal of cortical thinning abnormalities in the insula was reported posttreatment in low back pain patients that correlated with reduced pain.…”
Section: Discussionmentioning
confidence: 99%